Evaluating the Implementation of HACCP Systems in Food Establishments in Lapu-Lapu City, Cebu: Pathways to ISO 22000:2005 Certification - Payao, Analiza A.; Payao, Ronald B. (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
This descriptive-correlational study attempted to evaluate food safety procedures based on the Hazard Analysis Critical Control Point System (HACCP) among selected food establishments in Lapu-Lapu City, Philippines. A total of ninety-six (96) respondents who belong to personnel, supervisors, and managers of the food establishments participated in the data gathering. These respondents were selected purposively since the set criteria by the researchers should be strictly followed. Weighted mean and Chi-square were utilized to analyze the collected data using a survey questionnaire. Based on the findings, it was found that participating establishments achieved an 'outstanding' status, as evidenced by high satisfaction ratings from respondents, indicating their commitment to following HACCP as a standard protocol in meeting stakeholder expectations. Additionally, the perceptions of managers, supervisors, and personnel regarding food safety compliance were strongly aligned, highlighting a well-integrated and collaborative approach to maintaining food safety protocols. These results underscore the establishments’ commitment to regulatory compliance and customer satisfaction, providing insights into their readiness for higher standards such as HACCP implementation and ISO 22000:2005 certification.